Patterns of Limnohabitans microdiversity across a large set of freshwater habitats as revealed by Reverse Line Blot Hybridization - Jezbera, Jan; Jezberová, Jitka; Kasalický, Vojtěch; Šimek, Karel; Hahn, Martin W (PloS one, 2013)
Among abundant freshwater Betaproteobacteria, only few groups are considered to be of central ecological importance. One of them is the well-studied genus Limnohabitans and mainly its R-BT subcluster, investigated previously mainly by fluorescence in situ hybridization methods. We designed, based on sequences from a large Limnohabitans culture collection, 18 RLBH (Reverse Line Blot Hybridization) probes specific for different groups within the genus Limnohabitans by targeting diagnostic sequences on their 16 S-23 S rRNA ITS regions. The developed probes covered in sum 92% of the available isolates. This set of probes was applied to environmental DNA originating from 161 different European standing freshwater habitats to reveal the microdiversity (intra-genus) patterns of the Limnohabitans genus along a pH gradient. Investigated habitats differed in various physicochemical parameters, and represented a very broad range of standing freshwater habitats. The Limnohabitans microdiversity, assessed as number of RLBH-defined groups detected, increased significantly along the gradient of rising pH of habitats. 14 out of 18 probes returned detection signals that allowed predictions on the distribution of distinct Limnohabitans groups. Most probe-defined Limnohabitans groups showed preferences for alkaline habitats, one for acidic, and some seemed to lack preferences. Complete niche-separation was indicated for some of the probe-targeted groups. Moreover, bimodal distributions observed for some groups of Limnohabitans, suggested further niche separation between genotypes within the same probe-defined group. Statistical analyses suggested that different environmental parameters such as pH, conductivity, oxygen and altitude influenced the distribution of distinct groups. The results of our study do not support the hypothesis that the wide ecological distribution of Limnohabitans bacteria in standing freshwater habitats results from generalist adaptations of these bacteria. Instead, our observations suggest that the genus Limnohabitans, as well as its R-BT subgroup, represent ecologically heterogeneous taxa, which underwent pronounced ecological diversification.
Keywords: fyziologická adaptace; sladká voda; Water Microbiology; In Situ Hybridization, Fluorescence; mikrobiologie vody; RNA ribozomální 16S; bakteriální RNA; biodiverzita; koncentrace vodíkových iontů; hybridizace in situ fluorescenční; Biodiversity; Fresh Water; RNA, Bacterial; Comamonadaceae; RNA, Ribosomal, 16S; Hydrogen-Ion Concentration; Adaptation, Physiological